The Benefits of Development and Environmental Injustice - Geisinger, Alex (Columbia Journal of Environmental Law, 2019)
Professor of Law, Earle Mack School of Law, Drexel University. The author wishes to thank Roger Dennis, John Echeverria, Eileen Gauna, Robert Kuehn, and Bradford Mank, as well as participants in the Vermont Law School Environmental Colloquium and the Public Interest Law Center of Philadelphia Conference on Environmental Justice for their helpful comments and suggestions. Excellent research support was provided by Eric Brei, Alex Feldman, Seth Haynes, and Kimberly Magrini.